Clinical presentations and outcomes of celiac disease in children and adolescents at a tertiary care center in Lebanon - Andari, Dana; Hanna-Wakim, Rima; Khafaja, Sarah; Yazbeck, Nadine (Frontiers in Pediatrics, 2025)
IntroductionStudies on the clinical presentation of celiac disease and its impact on the growth of children in Lebanon are limited. The aim of this 10-year-retrospective study was to describe the common clinical presentations, diagnostic modalities, and the effect of the gluten-free- diet (GFD) on the growth of children and adolescents with celiac disease.MethodsThis was a retrospective chart review of subjects aged 6 months to 18 years who visited the Pediatric Gastroenterology clinic at the American University of Beirut Medical Center (AUBMC) between January 1, 2013, and June 30, 2023, and who were diagnosed with celiac disease based on serological markers and/or changes on histology of the small intestinal mucosal biopsies for those who underwent upper endoscopy, or HLA typing expressing the HLA-DQ2 or DQ8 gene for few subjects.ResultsThe study included 90 patients with celiac disease, of whom 64 were newly diagnosed during the study period. The mean age at diagnosis of celiac disease was 6.93 years. Females represented 60% of the pediatric subjects with celiac disease. The most common symptoms reported were abdominal pain (51.1%), weight loss or failure to thrive (45.6%), and diarrhea (24.4%). There was a significant increase in the mean weight-for-age Z-score (WAZ) and mean body mass index (BMI)-for-age Z-score (BMIZ) 12 months following initiation of GFD; however, the change in height-for-age Z-score (HAZ) at 12 months was not statistically significant. Half of the subjects were in remission at the last clinic follow-up.ConclusionThe most common symptoms that children with celiac disease in this cohort presented with are diarrhea, abdominal pain and failure to thrive. In this cohort, there was a significant increase in the weight parameters with no significant change in the height at 12 months after initiation of the GFD. The recognition of early manifestations, early diagnosis and strict adherence to the diet are of paramount importance to prevent long term complications.